Diagnosis and peculiarities of the treatment of pacemaker-mediated tachycardia - О.І. Семенюк; М.С. Сороківський; У.П. Черняга-Ройко; О.Й. Жарінов (Медицина неотложных состояний)
The purpose of this article is to analyze a clinical case of pacemaker-mediated tachycardia. It can develop only in patients with dual-chamber or biventricular pacemakers and preserved ventriculoatrial conduction. The mechanism of pacemaker-mediated tachycardia is re-entry between pacemaker and conduction system. A thorough examination of a patient, Holter ECG monitoring, and pacemaker interrogation are the main strategic approaches for correctly diagnosing PMT and differentiating it from other types of arrhythmias. To prevent the occurrence of PMT, it is necessary to be familiar with the antitachycardia algorithms of various pacemaker models. It is primarily recommended to always activate the algorithms for automatic detection and elimination of PMT, which is usually sufficient for the proper functioning of the device. If necessary, additional measures such as reprogramming the postventricular atrial refractory period and AV delay should be considered. With appropriate pacemaker programming, recurrences of PMT can mostly be avoided. The long-term prognosis for patients with PMT is favorable.